Sports - Hammond, Tim (New York Alfred A. Knopf)
Examines the equipment, rules, and background of many different team, target, and court sports, including soccer, rugby, Gaelic football, softball, cricket, ice hockey, table tennis, archery, and pool.
Include Color Illustration and Index
Keywords: Sports -- Photography of sports